2015
DOI: 10.21101/cejph.a4025
|View full text |Cite
|
Sign up to set email alerts
|

Severity, Causes and Outcomes of Traumatic Brain Injuries Occurring at Different Locations: Implications for Prevention and Public Health

Abstract: SUMMARYAim: Traumatic brain injuries (TBI) are a major public health problem. Although they are well studied, information on some aspects, such as the place of occurrence, is limited. The aim of this study was to describe the patterns of severity, causes and outcomes of TBI occurring at different locations and to identify the primary populations at risk of suffering TBI at each of the analysed locations.Methods: 1,818 patients with TBI admitted to hospitals in Austria, Slovakia, Croatia, Bosnia, and Macedonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that the context of the injury such as mechanism [ 20 ], place of occurrence of the injury [ 21 ], age group or social group [ 22 ] shows distinctive patterns as to severity, extent and overall outcome of TBI. In a similar manner we hypothesized that TBI will display distinctive patterns of cause, occurrence and outcome based on SES.…”
Section: Purposementioning
confidence: 99%
“…Previous studies have shown that the context of the injury such as mechanism [ 20 ], place of occurrence of the injury [ 21 ], age group or social group [ 22 ] shows distinctive patterns as to severity, extent and overall outcome of TBI. In a similar manner we hypothesized that TBI will display distinctive patterns of cause, occurrence and outcome based on SES.…”
Section: Purposementioning
confidence: 99%
“…Recent longitudinal studies have also demonstrated that sustained or worsening disordered behaviors and low self-esteem in adolescents are precursors of depressive symptoms [47,48]. It should be noted that depression in adolescence has been associated with negative attributional style, limited interpersonal relationships, increased likelihood of social isolation, and overall maladjustment as well as low self-esteem [49-51]. In addition, lower self-esteem and negative emotions in adolescents sequentially mediate the relationship between body dissatisfaction and disordered eating [52].…”
Section: Discussionmentioning
confidence: 99%
“…1,5,6 The variability of the diagnosis is a result of differing inclusion criteria and definitions of what constitutes an ABI or TBI. 7 ABI is often associated with comorbidities-for example, estimates indicate that as many as 70% of individuals have sustained concomitant injuries. 4,8 Regardless of whether an ABI is caused by traumatic or non-traumatic events, the clinical course is similar.…”
mentioning
confidence: 99%